Dual Sites for SEC11 on the SNARE SYP121 Implicate a Binding Exchange during Secretory Traffic. Issue 1 (8th March 2019) - Zhang, Ben; Karnik, Rucha; Alvim, Jonas; Donald, Naomi; Blatt, Michael R.
Abstract : The regulatory protein SEC11 binds differentially via two motifs on the Qa-SNARE SYP121 N terminus, only one of which overlaps with the K + channel-binding motif, to facilitate a binding exchange during SNARE complex assembly. Abstract: SNARE (soluble N -ethylmaleimide-sensitive factor attachment protein receptor) proteins facilitate vesicle traffic through their assembly in a heteromeric complex that drives membrane fusion. Much of vesicle traffic at the Arabidopsis ( Arabidopsis thaliana ) plasma membrane is subject to the Sec1/Munc18 protein SEC11, which, along with plasma membrane K + channels, selectively binds with the SNARE SYP121 to regulate its assembly in complex. How SEC11 binding is coordinated with the K + channels is poorly understood, as both SEC11 and the channels are thought to compete for the same SNARE binding site. Here, we identify a second binding motif within the N terminus of SYP121 and demonstrate that this motif affects SEC11 binding independently of the F 9 xRF motif that is shared with the K + channels. This second, previously unrecognized motif is centered on residues R 20 R 21 of SYP121 and is essential for SEC11 interaction with SYP121. Mutation of the R 20 R 21 motif blocked vesicle traffic without uncoupling the effects of SYP121 on solute and K + uptake associated with the F 9 xRF motif; the mutation also mimicked the effects on traffic block observed on coexpression of the dominant-negative SEC11 Ɗ149 fragment. We conclude that the R 20 R 21 motif represents a secondary site of interaction for the Sec1/Munc18 protein during the transition of SYP121 from the occluded to the open conformation that leads to SNARE complex assembly.